Desain Konten Multimedia untuk Media Sosial Kopi Leong: Pengaruh Visual terhadap Engagement dan Persepsi Merek Lokal - Rosanensi, Melati; Sumadewa, I Nyoman Yoga; Hasbullah, Hasbullah; Febri, Widia (STMIK BINA PATRIA, 2025)
Abstrak: This study aims to analyze the influence of multimedia content design on engagement levels and brand perception on Kopi Leong's social media accounts as a representation of a local brand. In the digital era, content visualization has become a strategic factor in building consumer identity and loyalty, especially for small and medium enterprises. This study uses a quantitative-descriptive approach involving 150 respondents who are followers of Kopi Leong's Instagram account. The research instrument is an online questionnaire that measures visual perception (color composition, typography, and visual style), engagement levels (likes, comments, and shares), and brand image (authenticity, trustworthiness, and local appeal). Data analysis was conducted using multiple linear regression to determine the relationship between visual variables on engagement and brand perception. The results show that visual design that consistent and authentic significantly increases engagement levels (p 0.05 ), and strengthens the brand's perception as a modern yet traditional local product. The warm color scheme and classic-style typography create a strong sense of familiarity and authenticity in the minds of consumers. In conclusion, multimedia content design plays a crucial role in strengthening Kopi Leong's branding strategy through social media, particularly in building audience engagement and strengthening the brand's local identity.